Study of primary stability of hip implant for semi hip replacement by using finite element analysis - Abdullah, Haslina; Zakaria, Mohamad Shukri; Talib, Norfazillah (2023)
One factor contributing to the failure of hip arthroplasty or hip surgery is the loosening of the hip implant. Loosening of the hip implant is assessed by primary stability that is associated with the relative displacement occurring at the interface between the bone and the implant. The geometrical of hip implant significance influences the primary stability. Hence, this paper investigated the effect of the geometry of the implant to the primary stability. A three-dimensional of femur was constructed based on the computed tomography dataset acquired from a Malaysian patient. In contrast, the type of hip implant was produced based on the dimension of the bone. The finite element method was implemented to simulate the primary stability based on normal walking conditions. Then, the primary stability is defined based on the differences of displacement at the interface of the bone and implant interface. From the analysis, it was found that rectangular hip implants led to the better stability at the proximal area and the tips distal end of the implant. It can be concluded that the finite element method predicted the implant’s primary stability and enhanced the surgery’s performance